Main Challenges in the Prevention of Prostate Cancer in Primary Health Care - , Thiago Augusto Ferreira dos Anjos; , Lucrecia Aline Cabral Formigosa; , Marcela Raíssa Asevedo Dergan; , Aline Moraes Monteiro; , Folve Ariel Garcia Alencar; , Thiago Simplício Costa; , Ana Paula Ferreira David; , Luciana Ferreira dos Santos (Archives of Current Research International, 2023)
Introduction: Prostate cancer is a public health problem and the second most common type of cancer in the male population. Objective: To report the experience of a health education action carried out by nursing students. Methodology: This is a descriptive study of the type experience report, carried out in November 2022, in a Family Health Strategy in the Municipality of Ananindeua, alluding to the Blue November, where a group of Nursing students addressed about men's health, elucidating about prostate cancer. Results: In the action in men's health, the active search was essential to relocate the individuals to the health unit, where the approach on the basic concepts of cancer, introduction to the disease, later correlating with prostate cancer (CA), where the male audience showed interest in the lecture, including interacting with the group, seeking to solve doubts about the disease, was highlighted. Conclusion: The approach in spite of cancer, therefore, is essential to the population, such as the male population, where information, debates and explanations about the subject generates knowledge and positive changes in health, in addition to the experience of nursing students was essential to share information in public health, especially about men's health.